2020
DOI: 10.1177/0022034520911647
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Bone Promotes Osseous Protection via Osteoclast Activation

Abstract: The current study aimed at investigating the long-term biological mechanisms governing bone regeneration in osseous defects filled with bovine bone (BB). Tooth extraction sockets were filled with BB or left unfilled for natural healing in a C57BL/6 mouse alveolar regeneration bone model ( n = 12). Seven weeks later, the alveolar bone samples were analyzed histologically with hematoxylin/eosin and tartrate-resistant acid phosphatase staining. A separate group ( n = 10) was used for RNA sequencing. Osteoclast in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…RvD1 also decreased osteoclast differentiation and activation in vitro and decreased bone and joint destruction in vivo (15). We also previously showed that RvD1 affected immune cells expression and decreased osteoclastogenesis in orthodontic tooth movement (16).…”
Section: Introductionmentioning
confidence: 56%
“…RvD1 also decreased osteoclast differentiation and activation in vitro and decreased bone and joint destruction in vivo (15). We also previously showed that RvD1 affected immune cells expression and decreased osteoclastogenesis in orthodontic tooth movement (16).…”
Section: Introductionmentioning
confidence: 56%
“…In contrast to conventional periodontal socket healing methods during OTM [9,[40][41][42], such as bone grafting, bone regeneration barrier membranes, and the application of plateletrich fibrin, PLGA-NfDs offer a targeted genetic intervention approach on the NF-κB pathway underlying periodontal formation and resorption, possibly providing a rather precise therapeutic strategy. Regarding the mechanisms of action, conventional methods often provide physical or biochemical support to aid periodontal regeneration [43], whereas the PLGA-NfDs provide a targeted decoy ODN approach that essentially inhibits specific genetic pathways associated with periodontal resorption, concurrently promoting periodontal formation in OTM.…”
Section: Discussionmentioning
confidence: 99%
“…After euthanization, the gingival mucosa and the springs were removed; maxillary bone specimens were collected, fixed in 4% paraformaldehyde overnight and dehydrated with 70% ethanol. Samples were scanned by the Micro CT scanner (µCT40 ® , SCANCO, Switzerland) at 70 kVp, 114µA intensity, and 1,000 projection at a 200-ms integration time, as previously described (24)(25)(26). Two-and threedimensional images were constructed.…”
Section: Evaluation Of the Effect Of Exogeneous Rvd1 On Otm Associate...mentioning
confidence: 99%